1999
DOI: 10.1074/jbc.274.25.17518
|View full text |Cite
|
Sign up to set email alerts
|

Specific Association of Megalin and the Na+/H+ Exchanger Isoform NHE3 in the Proximal Tubule

Abstract: We investigated whether the renal brush border Na ؉ /H ؉ exchanger NHE3 exists in assemblies with other proteins in native kidney membranes. To this end we generated monoclonal antibodies (mAbs) against affinity purified NHE3 protein complexes. Hybridomas were selected based on ability to immunoprecipitate NHE3. One of the resulting mAbs (10A3) labeled a high molecular mass (>200 kDa) protein and stained primarily the coated pit region of the proximal tubule in a manner similar to that described for megalin (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 47 publications
1
85
0
2
Order By: Relevance
“…These transporters are presumably located on microvilli (Fig. 2) and likely correspond to the fraction of exchangers that Biemesderfer et al (27) found not to associate with megalin. As such, these exchangers are most likely to function actively in ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…These transporters are presumably located on microvilli (Fig. 2) and likely correspond to the fraction of exchangers that Biemesderfer et al (27) found not to associate with megalin. As such, these exchangers are most likely to function actively in ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported an association between NHE3 and the putative scavenger receptor megalin in renal brush border membranes (1). Moreover, we found that renal brush border NHE3 exists in two states with distinct sedimentation coefficients, a 9.6 S megalin-free form and a 21 S megalin-bound form (1).…”
mentioning
confidence: 93%
“…Antibodies to NHE3-In a previous paper, we described in detail the development and characterization of isoform-specific monoclonal antibodies (mAbs) 1 to a restricted region of the carboxyl terminus of NHE3 (10). mAbs 2B9, 4F5, and 19F5 were raised to a fusion protein (fpNHE3-702-832) that reproduced the C-terminal 131 amino acids of rabbit NHE3 (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other molecules might be involved in the alteration of the subcellular distribution of NaPi-II. The mechanism for the internalization of NaPi-II might be distinct from the case of the Na ϩ /H ϩ exchanger, whereby specific association and co-internalization with megalin have been previously reported in the proximal tubules (28). Acute impairment of megalin function is often observed in renal tubulopathy caused by aminoglycosides and anticancer drugs (19,20).…”
Section: Discussionmentioning
confidence: 99%